2013
DOI: 10.3109/08820538.2013.835834
|View full text |Cite
|
Sign up to set email alerts
|

Scleral-Fixated Posterior Chamber Intraocular Lens Implantation in Pediatric and Adult Patients

Abstract: In both pediatric and adult patients, SFIOL implantation ends with favorable outcomes over the short term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…The third study subtype was of 10-0 polypropylene scleral-sutured PCIOLs that compared primary or secondary IOL implantation 7 or concomitant penetrating keratoplasty (PKP) versus non-PKP 8 or concomitant pars plana vitrectomy (PPV) versus concomitant anterior vitrectomy (AV). 9 Tables 1A, 1B, 1C, 1D, and 1E summarize the single surgical technique studies of 10-0 polypropylene scleralsutured PCIOL [10][11][12][13][14][15][16][17][18] (Table 1A), CV-8 polytetrafluoroethylene scleral-sutured PCIOL 19 (Table 1B), ISHF PCIOL in Table 1C, [3][4][5][20][21][22][23][24][25][26] 10-0 polypropylene irissutured PCIOL [27][28][29][30] (Table 1D), and iris-claw IOL [31][32][33][34][35][36][37][38][39][40] (Table 1E). The tables include months of follow-up and visual acuity outcomes for the studies.…”
Section: Published Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The third study subtype was of 10-0 polypropylene scleral-sutured PCIOLs that compared primary or secondary IOL implantation 7 or concomitant penetrating keratoplasty (PKP) versus non-PKP 8 or concomitant pars plana vitrectomy (PPV) versus concomitant anterior vitrectomy (AV). 9 Tables 1A, 1B, 1C, 1D, and 1E summarize the single surgical technique studies of 10-0 polypropylene scleralsutured PCIOL [10][11][12][13][14][15][16][17][18] (Table 1A), CV-8 polytetrafluoroethylene scleral-sutured PCIOL 19 (Table 1B), ISHF PCIOL in Table 1C, [3][4][5][20][21][22][23][24][25][26] 10-0 polypropylene irissutured PCIOL [27][28][29][30] (Table 1D), and iris-claw IOL [31][32][33][34][35][36][37][38][39][40] (Table 1E). The tables include months of follow-up and visual acuity outcomes for the studies.…”
Section: Published Resultsmentioning
confidence: 99%
“…However, a minority of studies was not consistent in BCVA reporting. Some studies contained only median BCVA, 14,43 a few did not include preoperative BCVA, 4,31,41,42,45,47 and others included only the percentage of eyes with 20/40 vision or better. 31,46 The 8-0 polypropylene scleral-sutured PCIOL authors 41 did not publish mean preoperative and postoperative BCVA.…”
Section: Visual Outcomesmentioning
confidence: 99%
“…22 There are no prospective randomized studies comparing outcomes between SFIOLs, ACIOLs, and IFIOLs in children, so decisions are based largely on surgeon preference and patient circumstance. Retrospective and longitudinal case series of children implanted with mainly sutured SFIOLs 2,27 38 have yielded promising short-term results at follow-ups ranging from 1 year to approximately 6 years, but concerns regarding glaucoma, endophthalmitis, lens decentration/dislocation, and need for additional surgery have steered some clinicians toward the use of aphakic spectacles or contact lenses as a first-line treatment in children. 39,40 Recently, IOL implantation via sutureless intrascleral (SIS) fixation has been performed in children with no lens dislocations after 6 months of follow-up, but long-term data are needed to more completely assess the efficacy and safety of this technique.…”
Section: Preoperative Considerationsmentioning
confidence: 99%
“…Anterior chamber or scleral fixated IOLs (SFIOLs) are most commonly used in IOL exchange. Serif et al and Burcu et al exchanged the majority of IOLs with SFIOLs (18,19) . Sturmer exchanged dislocated IOLs with ACIOLs and reported that postoperative intraocular pressure decompensation and vascular problems as major complications (20) .…”
Section: Discussionmentioning
confidence: 99%